What is the healthcare utilisation and out-of-pocket expenditure associated with osteoarthritis? A cross-sectional study. Issue 3 (9th March 2022) - Sibbritt, David; Sundberg, Tobias; Ward, Lesley; Broom, Alex; Frawley, Jane; Bayes, Jessica; Adams, Jon
Abstract : Objective: To examine the use and out-of-pocket expenses resulting from consultations, products and practices across conventional, self-care, and complementary medicine (CM) treatments for osteoarthritis (OA) among Australian women. Design, setting and participants: A cross-sectional survey of 800 women from the 45 and Up Study who had reported a clinical diagnosis of OA. Outcome measures: Women's use of conventional, CM and self-prescribed treatments for OA and the associated out-of-pocket cost. Results: Completed questionnaires were returned by 403 women (50.4%). Their average time since the first diagnosis of OA was 15.4 years, and self-rated severity of OA was 5.1 (out of 10) over the past 12 months. During the previous year, 67.0% of the women consulted a doctor, 39.2% consulted an allied health practitioner and 34.7% consulted a CM practitioner for their OA. Some women (19%) consulted with practitioner(s) from all three practitioner groups, 27% consulted with practitioner(s) from two of the three practitioner groups, while 6% consulted with a CM practitioner only. Women with a greater time since diagnosis had more consultations, as did women who rated their OA as more severe. Women's average combined out-of-pocket expenditure for OA-related healthcare consultations, prescription medications, products, and practices was $673 per annum. Extrapolated to all Australian women with OA, aged 50 years and over, the total out-of-pocket expenditure for this condition is estimated to be $873 million per annum. Conclusions: Australian women with OA use a range of conventional and CM consultations, self-care, products and practices to manage their condition, incurring significant out-of-pocket expenses. Given the high individual and societal burden of OA, there is a need for further research into the concurrent use of different healthcare resources with a view to providing safe, cost-effective management of OA across the healthcare system and the wider community.